2023
DOI: 10.54393/pjhs.v4i10.1026
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Nurse-led Educational Intervention on Therapeutic Communication of Undergraduate Nursing Students by Using SBAR tool

Aleena Ilyas,
Amjad Ali,
Tanseer Ahmed

Abstract: Efficient communication is most noteworthy because it impacts patient quality care. A prepared tool can useful to adequately impart patient data, lessen unfavorable incidents, improve patient safety, enhance quality of care, and amplify the healthcare team members’ satisfaction. Objective: To identify the effectiveness of nurse-led educational intervention on therapeutic communication of undergraduate nursing students by using the SBAR tool. Methods: This pre & post-quasi-experimental study was conducted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(2 reference statements)
1
1
0
Order By: Relevance
“…Findings of this study highlighted that majority of the participants were female. These ndings were similar to the studies conducted in Korea (2021), China (2021) and Korea in 2020, which showed the mostly highlighted participants were female [21][22][23]. In addition, our study found no signi cant difference between gender and SBAR tool score.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Findings of this study highlighted that majority of the participants were female. These ndings were similar to the studies conducted in Korea (2021), China (2021) and Korea in 2020, which showed the mostly highlighted participants were female [21][22][23]. In addition, our study found no signi cant difference between gender and SBAR tool score.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study showed that most of the study participants were enrolled in a two-year associate degree program. Whereas study conducted in Jordon in 2020, evident that most of the study par ticipants belonged to a four-year undergraduate program [21]. Our study found a signi cant difference between program enrolled of the participants and SBAR test score (p=0.032).…”
Section: Discussionmentioning
confidence: 40%